2021
DOI: 10.1093/europace/euab010
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal pattern of left atrial activation and asynchronous conduction predicted the occurrence of new atrial fibrillation: evidences for Bachmann’s bundle block in atrial fibrillation pathophysiology

Abstract: Aims Evidences suggest that recurrent atrial fibrillation (AF) is associated with left atrial (LA) remodelling. The goal of this study is to establish a method for assessment of LA remodelling and find predictors for the development of AF. Methods and results This prospective study included patients without a history of AF who were evaluated using pulsed-wave tissue Doppler imaging (PW-TDI). P-wave onset to A′-wave (PA′ inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The human atrial wall is a thin structure, with average measurements of wall thickness between 1 and 4 mm but with a broader range extending from 0.5 to 12 mm 19 . Furthermore, several studies have provided evidence for endocardial-epicardial voltage and activation asynchrony in patients with AF 8, 18, 20, 21 . BV, with its detection range limited to the endocardium or sub-endocardium -- sometimes within 1-2 mm deep layers, might not be optimal for capturing the complete substrate features of the entire layer.…”
Section: Discussionmentioning
confidence: 99%
“…The human atrial wall is a thin structure, with average measurements of wall thickness between 1 and 4 mm but with a broader range extending from 0.5 to 12 mm 19 . Furthermore, several studies have provided evidence for endocardial-epicardial voltage and activation asynchrony in patients with AF 8, 18, 20, 21 . BV, with its detection range limited to the endocardium or sub-endocardium -- sometimes within 1-2 mm deep layers, might not be optimal for capturing the complete substrate features of the entire layer.…”
Section: Discussionmentioning
confidence: 99%
“…upper area of the left atrium with delayed activation at the level of the mitral annulus, suggesting a blockage in the Bachmann bundle that connects the right atrium with the anterior-superior part of the left atrium, although genetically mediated electrical and structural family variants may also promote these different behaviors 17 . A recent work also using tissue Doppler in 98 patients with electrocardiographic signs of to the existence of blockade of the Bachmann´s fasciculus among whom many displayed hypertension and some ischemic disease, obtained assynchrony values in relation by comparing the activation of the septal and lateral wall thus obtaining cut-off values of 39+/-16 ms 18 . Seven days Holter recordings were carried out during the follow-up in symptomatic patients, resulting in 10% of patients with PAF, a similar result to that obtained by us (11%).…”
Section: Discussionmentioning
confidence: 99%
“…Preferential occurrence of conduction disorders in Bachmann's bundle was shown in patients with AF when compared to patients without a history of AF 11 . A recent study evaluating atrial activation sequence also showed a very strong association between conduction delay across Bachmann's bundle and new‐onset AF 12 . However, though van der Does et al showed concomitant reduction in voltage with aging, suggesting some degree of fibrosis of Bachmann's bundle, the exact substrate for conduction slowing, conduction heterogeneity and transverse conduction blocks remains to be investigated.…”
Section: Figurementioning
confidence: 99%